Medical Waste Management in Al-Basheer State Hospital - Current Situation and Future Prospects - Qteishat, Omar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the Middle East and North Africa Jordan is considered as the top medical tourism due to the high level of medical specialized medical centers in the country. In Jordan Ministry of Health monitors, evaluate, enforces, and regulates requirements of medical waste management over medical waste instructions No. 1/2001.
Keywords: Al Bashir Hospital; medical waste; waste incineration; medical waste management; Jordan; legislation; odpady medyczne; spalanie odpadów; gospodarka odpadami medycznymi; Jordania; regulacje prawne